2017
DOI: 10.1002/ijc.31107
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of programmed cell death‐ligand 1 expression and the immune microenvironment at the invasive front of colorectal cancers with high microsatellite instability

Abstract: Immunotherapy is reportedly effective in colorectal cancers (CRCs) with high microsatellite instability (MSI-H); however, the specific cell types that respond to immune checkpoint therapy are unclear. Herein, we aimed to examine the expression of programmed cell death-ligand 1 (PD-L1) and related proteins in MSI-H and microsatellite-stable (MSS) CRCs to investigate the immune microenvironment at the tumor's invasive front. The MSI status was retrospectively assessed in 499 patients undergoing surgical resectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 38 publications
4
33
0
Order By: Relevance
“…[44][45][46][47] Possible explanations for these conflicting results could be either technical issues (mainly Tissue Micro-Arrays vs whole tissue sections) and/or interpretation criteria (staining intensity, membranous vs cytoplasmic staining, tumor vs immune PDL1+ cells). Only the recent studies reported by Korehisa et al and Valentini et al 48,49 , based on whole tissue sections, are consistent with our results, showing that PDL1 expression should be evaluated on whole tissue sections to take into account its spatial heterogeneity. Furthermore, our results showing a significant association between PDL1 expression by immune cells, but not by e1562834-12 tumor cells, and the density of PD1+ TILs, suggest the importance of assessing the PDL1 expression pattern by immune cells, more frequent than the tumor cell pattern in CRC (except in medullary carcinomas), to better appreciate its biological impact on the antitumor immune response.…”
Section: Discussionsupporting
confidence: 93%
“…[44][45][46][47] Possible explanations for these conflicting results could be either technical issues (mainly Tissue Micro-Arrays vs whole tissue sections) and/or interpretation criteria (staining intensity, membranous vs cytoplasmic staining, tumor vs immune PDL1+ cells). Only the recent studies reported by Korehisa et al and Valentini et al 48,49 , based on whole tissue sections, are consistent with our results, showing that PDL1 expression should be evaluated on whole tissue sections to take into account its spatial heterogeneity. Furthermore, our results showing a significant association between PDL1 expression by immune cells, but not by e1562834-12 tumor cells, and the density of PD1+ TILs, suggest the importance of assessing the PDL1 expression pattern by immune cells, more frequent than the tumor cell pattern in CRC (except in medullary carcinomas), to better appreciate its biological impact on the antitumor immune response.…”
Section: Discussionsupporting
confidence: 93%
“…14 However, MSI tumors highly up-regulate expression of multiple immune checkpoints. 11,30 Consistently, our study demonstrated that MSI-H CRCs displayed PD-1/PD-L1 overexpression, which might help CRC cells to survive from naturally immune eradication. Moreover, we found that MSI-H patients with PD-1/PD-L1 upregulation developed poorer survival than those with PD-1/PD-L1 downregulation, which may potentially define subsets of CRC that might be more sensitive to checkpoint blockade.…”
Section: Discussionsupporting
confidence: 77%
“…4 Moreover, it has been recently demonstrated that, on the basis of higher expression of programmed death-ligand 1 (PD-L1) and a higher level of BRAF mutation, hmMSI-H patients are candidates for immune checkpoint and tyrosine kinase inhibitors, respectively. 12,13 In contrast, the frequency of KRAS mutation in SAC is even higher than in CC, 14,15 and most SACs are microsatellite-stable, making them refractory to anti-epidermal growth factor receptor or anti-PD-L1 agents. Therefore, the aim of this study was, by using molecular profiling, to ascertain which molecular features are responsible for such differences between SAC and hmMSI-H, with a view to identifying useful diagnostic biomarkers and potential molecular targets.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, hmMSI‐H is characterised by the occurrence of a Crohn‐like reaction and peritumoral and intratumoral infiltrates . Moreover, it has been recently demonstrated that, on the basis of higher expression of programmed death‐ligand 1 (PD‐L1) and a higher level of BRAF mutation, hmMSI‐H patients are candidates for immune checkpoint and tyrosine kinase inhibitors, respectively . In contrast, the frequency of KRAS mutation in SAC is even higher than in CC, and most SACs are microsatellite‐stable, making them refractory to anti‐epidermal growth factor receptor or anti‐PD‐L1 agents.…”
Section: Introductionmentioning
confidence: 99%